Whole-body 18-F-FDG-PET in patients with leptomeningeal disease and correlation with MRI. Issue 2 (February 2021) - Panda, Ananya; Hintermeister, Holly A.; Hunt, Christopher H.; Kendi, Ayse Tuba
Abstract : Objective: Studies evaluating leptomeningeal disease on whole-body 18F-FDG PET are lacking. The purpose was to evaluate PET imaging of leptomeningeal disease and investigate the incremental utility of newer PET reconstructions in leptomeningeal disease. Methods: PET imaging of 56 patients with leptomeningeal disease detected initially on MRI ( n = 53) or cytopathology ( n = 35) were retrospectively reviewed. Regular 3-dimensional iterative reconstruction (3D IR, n = 56) and advanced reconstruction (AdvRecon, n = 41) PET images were evaluated by readers blinded to clinical and MRI findings for uptake involving cauda equina, posterior fossa and spinal cord. Spinal cord uptake pattern was classified as normal (uptake < liver), uptake = liver, conus uptake > liver, conus and cervical cord uptake > liver and multifocal/diffuse uptake > liver. SUVmax ratios of conus/liver, conus/left atrium and conus/cervical cord were compared between 3D IR and AdvRecon datasets. Results: Cauda equina uptake was seen in 64% and 78% on 3D IR and AdvRecon; posterior fossa uptake was seen in 52% and 54% on 3D IR and AdvRecon, respectively. Twelve percent had cauda equina or posterior fossa uptake visible only on AdvRecon. On 3D IR, normal spinal cord uptake was most common (27%); on AdvRecon, conus and cervical cord uptake > liver was most common (32%). Seven of 11 patients with normal spinal cord uptake on 3D IR were upgraded to increased uptake on AdvRecon. AdvRecon showed significantly higher conus/liver, conus/blood pool and conus/cervical cord SUVmax ratios ( P < 0.0001). Conclusion: Abnormal uptake in cauda equina, posterior fossa and spinal cord uptake are visible on FDG PET in leptomeningeal disease with increased conspicuity advanced PET reconstructions. Abstract : Supplemental Digital Content is available in the text.